2023
DOI: 10.1002/pro.4603
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insight into the specific interactions of the SARS‐Coronavirus‐2 nucleocapsid with RNA and host protein

Abstract: The severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) nucleocapsid protein is the most abundantly expressed viral protein during infection where it targets both RNA and host proteins. However, identifying how a single viral protein interacts with so many different targets remains a challenge, providing the impetus here for identifying the interaction sites through multiple methods. Through a combination of nuclear magnetic resonance (NMR), electron microscopy, and biochemical methods, we have charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…In order to investigate possible changes in backbone conformation, 13 C α chemical shifts of pSR were compared to recently proposed random coil chemical shift values ( 64 , 65 ) for pN234(III), indicating that no significant induction of secondary structure results from hyperphosphorylation (supporting figure 1), as previously proposed for PKA-phosphorylated N (residues 1-209) ( 45 ).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In order to investigate possible changes in backbone conformation, 13 C α chemical shifts of pSR were compared to recently proposed random coil chemical shift values ( 64 , 65 ) for pN234(III), indicating that no significant induction of secondary structure results from hyperphosphorylation (supporting figure 1), as previously proposed for PKA-phosphorylated N (residues 1-209) ( 45 ).…”
Section: Resultsmentioning
confidence: 92%
“…The broadly phosphorylating protein kinase A (PKA) has been exploited to phosphorylate N in a single step, including via co-expression with N ( 45 ), and notably to investigate the impact on binding of the host factor 14-3-3 ( 66 ). Incubation of N with PKA in vitro results in phosphorylation of six sites in the SR region of N234 (supporting figure 4) whose backbone resonances were assigned, namely pS180, pS193, pS194, pS197, pS201 and pS202, although broader phosphorylation was observed by co-expression with PKA ( 45 , 66 ). This 6-fold phosphorylated form of N234 nevertheless maintains its binding to RNA (figure 5B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since HSF1 regulates the expression of a broad change of proteostasis factors ( 45 47 ), potential candidates include heat shock proteins that can bind to the partially folded conformation and prevent aggregation, and folding enzymes such as peptidyl prolyl isomerases that catalyze the often rate-limiting steps of protein folding. It has been observed that the NP of severe acute respiratory syndrome coronavirus 2 virus heavily interacts with peptidyl prolyl isomerases, such as cyclophilin A and peptidyl-prolyl cis - trans isomerase never-in-mitosis-gene-A-interacting 1 (Pin1), although it is not yet clearly known whether these enzymes play an important role in NP folding ( 48 ). The chaperones that can rescue Pro 283 NP may have homologous proteins in E. coli, because Pro 283 NP could be recombinantly expressed in E. coli without a noticeable yield decrease compared to Ser 283 NP.…”
Section: Discussionmentioning
confidence: 99%